Sejarah Berdirinya Pondok Pesantren Darul Istiqomah Bojonegoro sebagai Lembaga Pendidikan - M. Fani Burhan Firmansyah (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2024)
This article discusses the history of the establishment of Pondok Pesantren Darul Istiqomah Bojonegoro as an educational institution. Darul Istiqomah Islamic Boarding School was founded in 1996 by KH. Abdul Hamid Saifuddin Zuhri Al Musyafa or better known as Kh. Saifuddin. Previously, Kh. Saifuddin had established Assulaiman Islamic Boarding School in 1984 in Nglumber Village. In its heyday, Assulaiman Islamic Boarding School had many students. But in 1994, Kh. Saifuddin decided to close the Assulaiman Islamic Boarding School because he experienced obstacles in preaching. Then he moved to Woro Village and established a new boarding school called Darul Istiqomah Islamic Boarding School. This article also discusses the biography of the boarding school caregiver, Kh. Saifuddin and the development of Darul Istiqomah Islamic Boarding School until now.